Optimal Allocation and Sizing of Distributed Generation in Distribution System via Firefly Algorithm - Mohd Wazir, Mustafa; M. H., Sulaiman; Omar, Aliman; Siti Rafidah, Abdul Rahim; A., Azmi (IEEE, 2012)
This paper presents an application of Firefly Algorithm (FA) in determining the optimal location and size of Distributed Generation (DG) in distribution power networks. FA is a meta-heuristic algorithm which is inspired by the flashing behavior of fireflies. The primary purpose of firefly’s flash is to act as a signal system to attract other fireflies. In this paper, IEEE 69-bus distribution test system is used to show the effectiveness of the FA. Comparison with other method is also given.